Through the Wall Human Signature Detection using Principle Component Analysis (PCA) - Singh V.; Bhattacharyya S.; Jain P.K. (My University, 2025)
Life sign signal detection through the wall suffers from strong clutter due to the boundary of a dielectric wall and other environmental noises. Principle component analysis (PCA) method is applied to enhance the information of a life target beyond the boundary by suppressing the undesired clutter. The effect of this clutter reduction makes the low-frequency variation of heartbeat detectable in further moving target indicator (MTI) processing step. The detection result of a human subject is represented in a Range-Doppler plane, from which the location and the characteristics of the subject have been determined. © 2018 IEEE.